A comparison of cost-effectiveness of computer-assisted 2-and 3-dimensional planning techniques in orthognathic surgery. Issue 4 (May 2019) - Bengtsson, M.; Wall, G.; Becktor, J.P.; Rasmusson, L.
Abstract: The aim of this randomised controlled trial was to compare the costs and benefits of computer-based 2-dimensional and 3-dimensional predictions in orthognathic surgery. Subjects aged 18–30 years with severe class III malocclusion had their treatment planned with both 2- and 3-dimensional techniques. They were randomised in a 1:1 ratio for one or other planning technique. Costs (financial, time, and dose of radiation) were compared with benefits (accuracy and health-related quality of life (HRQoL)). In total, 57 subjects (27 women and 30 men, mean (range) age 21 (18–28) years) completed the study. Comparisons showed no significant difference in total time spent, but a large advantage for the 2-dimensional technique in financial costs (p < 0.001); it also required a significantly lower dose of radiation (p < 0.001). The cost-effectiveness analysis showed a reduction in time of 0.53 minutes/HRQoL-point gained, and an increased economic cost of US$15/HRQoL point gained for the 3-dimensional technique. It also showed that the two techniques consumed an equal amount of time, but that the 2-dimensional technique had lower financial costs, and the 3-dimensional technique a larger dose of radiation.